Changing consumption patterns and roles of pulses in nutrition, and future demand projections - Kumar, Praduman; Joshi, Pramod Kumar; Parappurathu, Shinoj (International Food Policy Research Institute, 2017)
In this chapter we study the dynamics of consumption of pulses and assess pulses’ nutritional role with a focus on proteins. We note variations among different income strata, highlighting the higher protein deficiency among low-income groups and the higher price responsiveness of poorer consumers. We discuss the likely ineffectiveness of targeted consumer subsidies. Subsequently, using demand-system estimation, we make projections for the demand for pulses in India to 2030.